2019
DOI: 10.1097/dcr.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Management of Malignant Large-Bowel Obstruction

Abstract: CASE SUMMARY: An otherwise healthy 59-year-old man presented to the emergency department with 2 weeks of narrowed stools, 5 days of obstipation, and 1 day of abdominal pain, nausea, and vomiting. Computed tomography revealed an obstructing sigmoid mass without evidence of metastatic disease, and the CEA was 1.2 ng/mL. Flexible sigmoidoscopy confirmed a circumferentially obstructing distal sigmoid neoplasm. Endoscopic stent placement was immediately followed by a firm distended abdomen. An upright r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…There was one incidence of abdominal pain after SEMS insertion, but only for observing without special handling. Not all lesions are anatomically amenable to stenting, including those in the distal rectum that preclude deployment in normal bowel distal to the tumor [ 25 ], even if the stent is released and decompression successfully; the rectal irritation can also be very severe, and one patient chose to remove the stent for transverse colostomy because of serious rectal irritation symptom. Therefore, we always excluded rectal cancers within 6 to 8 cm of the anal verge in our center, except for very special and necessary cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one incidence of abdominal pain after SEMS insertion, but only for observing without special handling. Not all lesions are anatomically amenable to stenting, including those in the distal rectum that preclude deployment in normal bowel distal to the tumor [ 25 ], even if the stent is released and decompression successfully; the rectal irritation can also be very severe, and one patient chose to remove the stent for transverse colostomy because of serious rectal irritation symptom. Therefore, we always excluded rectal cancers within 6 to 8 cm of the anal verge in our center, except for very special and necessary cases.…”
Section: Discussionmentioning
confidence: 99%
“…The usage limitation is the high perforation rate in several randomized controlled trials [ 23 , 37 , 38 ], other complications, and environmental health threats to operators by long-term exposure under X-ray [ 1 ]. The variation in the rates of success of SEMS insertion and associated complications reported in the literature suggests that individual expertise, institutional experience, and available resources [ 25 ] have a significant bearing on the clinical application of SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical advantages of SEMS insertion in the management of ACO combined with the little negative oncological consequences makes stent a effective clinical method [4] . The limitation of the use of SEMS is the high perforation rate in several randomised controlled trials [24,33,34] , other complications, technical and clinical success rate need to improve for some units, long term exposure under X-ray environmental threats health to operators, especially young doctor [1] et al The variation in the rates of success of SEMS insertion and associated complications reported in the literature suggests that individual expertise institutional experience and available resources [26] has a signi cant bearing on the clinical application of SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…There was one incidence of abdominal pain after SEMS insertion, but only for observing and the patient did not need special handling. Not all lesions are anatomically amenable to stenting, including those in the distal rectum that preclude deployment in normal bowel distal to the tumor [26] , and even if stent is released and decompression successfully, the rectal irritation can also be very severe. Many distal rectum obstruction patients who accepted stent insertion complained of obvious discomfort, and one patient chose to remove the stent for transverse colostomy because of serious rectal irritation symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches can still be offered to patients that are being treated with palliative care in certain conditions, including no symptomatic resolution within 2-3 days following the administration of conservative treatment, only one site is obstructed, and the patient is in a suitable physical condition. 21 Besides, the chances even increase in patients suffering from benign obstruction because studies have demonstrated that the outcomes are more favorable with these patients. 7,8,14,22,23 Figure 1 summarizes the approaches that should be done when managing patients with large bowel obstruction.…”
Section: Managementmentioning
confidence: 99%